2016
DOI: 10.1002/marc.201600476
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Deactivation of Enzymes by Redox‐Responsive Nanogel Carriers

Abstract: Novel redox-responsive polymeric nanogels that allow highly efficient enzyme encapsulation and reversible modulation of enzyme activity are developed. The nanogel synthesis and encapsulation of enzyme are performed simultaneously via in situ crosslinking of pyridyldisulfide-functionalized water-soluble reactive copolymers, which are synthesized via reversible addition-fragmentation chain transfer copolymerization. Obtained nanogels with loaded cellulase demonstrate very good colloidal stability in aqueous solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…A modified version of thiol-disulfide exchange between thiols and activated disulfides (e.g., pyridyl disulfide) proceeds faster than thiol oxidation to form disulfides, and has been applied to polymer crosslinking to form nanogels within hours [41]. Recent examples include the work by Peng et al that demonstrated the crosslinking of pyridyl disulfide-presenting copolymers with four-armed, thiol-terminated linkers [42]. The disulfide-crosslinked nanogels were used for the encapsulation and deactivation of a cellulase.…”
Section: Substitution Reactions Of Thiols For Hydrogel Crosslinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified version of thiol-disulfide exchange between thiols and activated disulfides (e.g., pyridyl disulfide) proceeds faster than thiol oxidation to form disulfides, and has been applied to polymer crosslinking to form nanogels within hours [41]. Recent examples include the work by Peng et al that demonstrated the crosslinking of pyridyl disulfide-presenting copolymers with four-armed, thiol-terminated linkers [42]. The disulfide-crosslinked nanogels were used for the encapsulation and deactivation of a cellulase.…”
Section: Substitution Reactions Of Thiols For Hydrogel Crosslinkingmentioning
confidence: 99%
“…Crosslinking of pyridyl disulfide-presenting polymer self-assembly with thiol-terminated linkers for the encapsulation and deactivation of a cellulase. Image modified with permission from [42]. Copyright 2016 Wiley.…”
Section: Figurementioning
confidence: 99%
“…It is well‐known that disulfide bonds can be simply cleaved and reformed in the presence of reducing agents and oxidants under mild conditions, respectively . As a consequence of this reversible reaction, disulfide crosslinked polymer gels have attracted increased attention and been widely reported for numbers of applications, such as drug release and enzyme immobilization . N , N ‐bis(acryloyl cystamine) (BAC), a disulfide‐contained crosslinker, has been extensively employed to endow reversibility or partial/complete degradation in hydrogels for PNiPAAm and polyacrylamide (PAAm) .…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] As a consequence of this reversible reaction, disulfide crosslinked polymer gels have attracted increased attention and been widely reported for numbers of applications, such as drug release and enzyme immobilization. [36][37][38][39][40][41] N,N-bis(acryloyl cystamine) (BAC), a disulfide-contained crosslinker, has been extensively employed to endow reversibility or partial/complete degradation in hydrogels for PNiPAAm and polyacrylamide (PAAm). [42][43][44] Moreover, combining with commonly used crosslinker N,N-methylenebis(acrylamide) (BIS), a partially degradable and reversible hydrogel system can be achieved.…”
mentioning
confidence: 99%
“…Investigations of alternative carriers such as nano- or microgels for immobilization of catalysts in general and enzymes in particular attracted more and more interest during the last years [23,24]. Hereby, the influence of the gel network on the enzymatic activity and the protection against solvents are important research issues among others [25,26,27]. Recently, we reported about the synthesis and immobilization of CaLB in tailormade microgels and showed the influence of the microgel polarity on the ring-opening polymerization activity of CaLB [28,29,30].…”
Section: Introductionmentioning
confidence: 99%